Analysis of Production Factor Efficiency in Organic Rice Farming (Oryza sativa) (A Case in Sukorejo Village, Sambirejo Sub-district, Sragen District) - Novil Dedy Andriatmoko (HABITAT, 2020)
Central Java Province is the third largest rice producer in Indonesia (BPS, 2019). Sragen Regency has started developing organic rice since 2010 and the slogan for agriculture is "Go Organic". Sukorejo Village is one of the villages in Sambirejo sub-district as the center of organic rice production which is still under development. The problem faced is a low productivity due to a limited availability of production factors i.e. fertilizer and bio pesticides. It is engendered by the majority of farmers provide input traditionally. The allocative efficiency using the regression coefficient value of Cobb-Douglass was applied to analyze the efficiency of those production factors. The result of analysis showed that the value of using bio pesticides has not been efficiently obtained by NPMx/Px of 2.66. It displayed that the allocation use of the bio pesticides was still dearth of. The respondents used pesticides at 54 Lt/ha in average have not been efficient, therefore it needs to be enumerated to get the maximum production reaching 104.04 Lt/ha. While, the results of analysis revealed that the value of NPMx/Px allocation of labor was 1.28 in which the value was greater than one so that the allocation of labor in the study area was not efficient. With the use of labor at 93.6 HOK per hectare in one planting season, it indicated that the allocation was still inefficient. Farmers need to add the optimal use of labor to reach 120.25 HOK per hectare in one planting season.